Pengaruh Harga dan Kualitas Produk terhadap Minat Beli Masyarakat Secara Online pada Masker Wajah Organik di Kota Denpasar - RIZKYTA, FIRSTNANDA ASHRY; WIJAYANTI, PUTU UDAYANI; DEWI, IDA AYU LISTIA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.12, No.2, Desember 2023, 2023)
The Influence of Price and Product Quality toward Society Purchasing Intention Internet Online on Organic Face Masks in Denpasar City.  One of the organic agricultural products that can be processed into beauty products is a face mask. The number of companies that issue various types of products, makes consumers have many choices to buy organic face mask products. The purpose of this study is to determine and analyze the influence of price and product quality toward society purchase intention internet online on organic face masks in Denpasar City. The types of data used are quantitative and qualitative data. The sample in this study amounted to 96 respondents using purposive sampling technique. Data analysis was carried out using the SEM-PLS approach. The results of this study indicate that the price and product quality variables have a positive and significant effect on people's online buying interest in organic face masks in Denpasar City. The price variable shows that price affordability is the highest parameter, this proves that organic face masks that are sold can be purchased by all groups. The product quality variable shows the highest durability parameter. The durability in this study is seen from the durability of the packaging, this proves that the packaging of organic face masks sold is good, durable, not easily damaged and dirty. Suggestions for online shop owners for organic face masks should pay attention and improve the quality of their products, such as the function of the organic face masks themselves so that purchase intention increases.